THE ANXIETY EXPERIENCED BY THIRD-YEAR STUDENT TEACHERS AT FELTE, ULIS WHILE DELIVERING MICRO-TEACHING LESSONS = SỰ LO LẮNG CỦA SINH VIÊN NĂM THỨ 3 TẠI KHOA SƯ PHẠM TIẾNG ANH, TRƯỜNG ĐẠI HỌC NGOẠI NGỮ KHI THỰC HIỆN GIẢNG DẠY VI MÔ - Bùi, Việt Vương (2020)
The purpose of this research paper is to examine the anxiety that the third-year student teachers at FELTE, ULIS experience while they deliver their micro-lessons, an issue related to micro-teaching which has not been thoroughly addressed so far in this research context. Similar to any other teaching professions, sufficient practice is of great importance to English Language student teachers before they assume the roles of real teachers. With the aim of preparing teacher trainees for their future teaching practice, micro-teaching, a widely recognized teacher training method, is integrated into many courses such as EFL/ESL Classroom Techniques and Practices (ELT2), Lesson Planning and Material Development (LPMD) at FELTE, ULIS, VNU. From the perspective of the researcher, although micro-teaching is a beneficial training method, factors such as anxiety can potentially reduce its efficacy. With the use of survey questionnaires and semi-structured interviews, along with the participation of 124 third-year prospective teachers, this study finds that the concerns about time limit when collaborating with peers, teachers’ rapport and support, mock students’ high language proficiency, peer pressure, artificiality of the lesson, and problems with the facilities and equipment are the main anxiety-inducing factors. The anxiety resulting from such sources can adversely influence the performance of the teacher trainees in their microteaching in terms of language proficiency and teaching competence. From this reality, recommendations are made based on student teachers’ suggestions to reduce the unwanted anxiety and further improve the effectiveness of micro-teaching.